Some associative algebras related to U(g) and twisted generalized Weyl algebras - Mazorchuk, V.; Ponomarenko, M.; Turowska, L. (MATHEMATICA SCANDINAVICA, 2003)
We prove that both Mickelsson step algebras and Orthogonal Gelfand-Zetlin algebras are twisted generalized Weyl algebras. Using an analogue of the Shapovalov form we construct all weight simple graded modules and some classes of simple weight modules over a twisted generalized Weyl algebra, improving the results from [6], where a particular class of algebras was considered and only special modules were classified.